Hypersensitivity pneumonitis in Covid-19: mortality, risk factors, and clinical outcomes from a 30-case observational study - Ozgun Niksarlioglu, Elif Yelda; Uysal, Mehmet Atilla; Seyhan, Ekrem Cengiz; Kıyık, Murat; Çetinkaya, Erdoğan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
.